2017
DOI: 10.1021/acscatal.7b01643
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Transfer versus Methylation: On the Genesis of Aromatics Formation in the Methanol-To-Hydrocarbons Reaction over H-ZSM-5

Abstract: The catalytic conversion of methanol (MeOH) and dimethyl ether (DME) into fuels and chemicals over zeolites (MTH process) is industrially emerging as an alternative route to conventional oil-derived processes. After 40 years of research, a detailed mechanistic understanding of the intricate reaction network is still not fully accomplished. The overall reaction is described as two competitive catalytic cycles, dominated by alkenes and arenes, which are methylated and cracked or dealkylated to form effluent prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 66 publications
3
96
0
Order By: Relevance
“…To gain insight in the proximity between these two acid functionalities, two-dimensional where methanol can act as hydrogen donor. Proton transfer occurs on both BAS 25 and extraframework aluminium species. 26 The sharp decrease in formation of ethylene and aromatics in sample Z3 suggests the almost full suppression of the aromatic cycle.…”
mentioning
confidence: 99%
“…To gain insight in the proximity between these two acid functionalities, two-dimensional where methanol can act as hydrogen donor. Proton transfer occurs on both BAS 25 and extraframework aluminium species. 26 The sharp decrease in formation of ethylene and aromatics in sample Z3 suggests the almost full suppression of the aromatic cycle.…”
mentioning
confidence: 99%
“…Briefly, the studies revealed a key role of methanol and DME as hydrogen‐transfer agents between the alkene and arene cycles, as well as between monocyclic arenes and heavier analogues . Furthermore, hydrogen‐transfer reactions were found to take place at the Brønsted acid sites, whereas isolated Lewis acid sites had negligible activity for both the methylation and hydrogen‐transfer reactions . The role of Lewis acid sites in MTH is still not fully revealed.…”
Section: Resultsmentioning
confidence: 99%
“…Methane formation from two DME molecules via a methoxy methylene species was recently directly linked to the formation of the first C−C bond in the MTH reaction . Whereas such a direct hydrogen transfer between two oxygenate molecules is feasible, the activation energy of this reaction is far higher than that for hydrogen transfer from a DME or methanol molecule to an adjacent alkene molecule . Methane formation associated with the MTH initiation reaction is, therefore, assumed to take place mainly in the first part of the reactor, in which the concentration of hydrocarbons is negligible .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, commercial HZSM‐5 cannot obtain BTX with a considerable selectivity in MTA reaction due to the limitation of pore channel, acidity and morphology of catalyst . Meanwhile there was a large amount of amorphous silicon on outer surface and channel, which would result in a decrease of catalyst activity.…”
Section: Introductionmentioning
confidence: 99%